2016
DOI: 10.1016/j.jpain.2016.01.475
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Central Sensitization in Patients With Sickle Cell Disease

Abstract: Central sensitization (CS), nociceptive hyper-excitability known to amplify and maintain clinical pain, has been identified as a leading culprit responsible for maintaining pain in several chronic pain conditions. Recent evidence suggests that it may explain differences in the symptom experience of individuals with sickle cell disease (SCD). Quantitative sensory testing (QST) can be used to examine CS and identify individuals that may have a heightened CS profile. The present study categorized patients with SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 58 publications
7
78
2
2
Order By: Relevance
“…Murine SCD models and individuals with SCD show increased sensitivity to experimental pain similar to that described in other groups with chronic pain [12, 1618]. Recent murine and human studies have observed central sensitization in SCD [10, 14, 1822]. Central sensitization is a process where repeated nociceptive signals from the periphery affect and alter pain processing in the central nervous system, leading to amplification of pain.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Murine SCD models and individuals with SCD show increased sensitivity to experimental pain similar to that described in other groups with chronic pain [12, 1618]. Recent murine and human studies have observed central sensitization in SCD [10, 14, 1822]. Central sensitization is a process where repeated nociceptive signals from the periphery affect and alter pain processing in the central nervous system, leading to amplification of pain.…”
Section: Introductionmentioning
confidence: 72%
“…Tests of temporal summation are being considered as potential clinical assessment tools for characterizing central sensitization in other chronic pain conditions [41, 42], although central sensitization is not uniformly observed in chronic pain [14, 43]. Temporal summation is specific for increased responses by spinal dorsal horn or other central neurons to painful stimuli [41, 44, 45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sickle Cell Disease -Pain and Common Chronic Complications 74 patients was recently evaluated using QST, questionnaires and daily pain diaries [29]. Those patients with higher scores for central sensitization exhibited worse manifestations of SCD.…”
Section: Mechanisms Of Pain In Sickle Cellmentioning
confidence: 99%